2020
DOI: 10.26676/jevtm.v4i1.106
|View full text |Cite
|
Sign up to set email alerts
|

Hate to Burst Your Balloon: Successful REBOA Use Takes More Than a Course

Abstract: Background: Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) is emerging as a viable intervention for hemorrhagic shock. Training surgeons to place the device is only part of the process. We hypothesize that implementation challenges extend beyond surgical skills training and initial REBOA use should not be expected to mirror published success.Methods:All REBOA placements from January 2016-February 2017 at a level 1 trauma center were reviewed for opportunities for improvement (OFI). Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
(36 reference statements)
0
23
0
1
Order By: Relevance
“…The use of REBOA should take into account skills, high expertise on their applicability [ 47 , 48 ], acceptability of clinicians and cost [ 49 , 50 ]. For optimal success, REBOA requires careful system-wide multidisciplinary implementation [ 51 ].…”
Section: Limitationsmentioning
confidence: 99%
“…The use of REBOA should take into account skills, high expertise on their applicability [ 47 , 48 ], acceptability of clinicians and cost [ 49 , 50 ]. For optimal success, REBOA requires careful system-wide multidisciplinary implementation [ 51 ].…”
Section: Limitationsmentioning
confidence: 99%
“…REBOA use in trauma patients and others is a welldescribed technique to assist in managing, and in some cases preventing, potential catastrophic bleeding [6,7]. As indications for the use of REBOA in the management of life-threatening haemorrhage grow and its popularity amongst clinicians increases, more complications can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to a thoracotomy, Romagnoli et al 3 found in REBOA patients it took >2 additional minutes to occlude the aorta, a delay that could be crucial in a crashing patient. In a retrospective review of data from a level 1 trauma center, Theodorou et al 4 found that ∼44% of REBOA patients developed significant post‐procedural complications.…”
Section: Could We?mentioning
confidence: 99%